Bye, Bye Financial Repression, Hello Financial Deepening: The Anatomy of a Financial Boom - Jo\~ao Manoel P. De Mello; Márcio G. P. Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2011)
Since the conquest of hyperinflation, with the Real Plan, in 1994, the Brazilian financial system has grown from early infancy to late adolescence. We describe the process of maturing with emphasis on the defining features of the Brazilian financial system over the last 20 years: 1) stabilization and the subsequent financial crisis; 2) universality of banks; 3) market segmentation through public lending; 4) institutional improvement. Further paraphrasing Díaz Alejandro (1984), we raise some hypotheses on why, this time, the financial boom has not (at least yet) turned into a financial crash.
Keywords: G21; G28; G32; 330; Financial repression; financial deepening; stabilization; stability; financial crisis; stability. Jel Codes: G21; G28; G32; Finanzsystem; Universalbank; Finanzkrise; Brasilien